In vitro 3D and gravimetric analysis of removed tooth structure for complete and partial preparations. Issue 2 (April 2019) - Monaco, C.; Arena, A.; Štelemėkaitė, J.; Evangelisti, E.; Baldissara, P.
Abstract: Purpose: To quantify and to compare a gravimetric and three-dimensional (3D) analysis of the removed tooth structure for different complete crown preparations. Methods: A total of 80 molar resin teeth and 8 preparation finishing lines were chosen: 1 for metal ceramic crowns (MCC); 3 for zirconia all-ceramic crowns: knife edge (ZirKnE), chamfer (ZirCha), and shoulder (ZirSho); 4 for lithium disilicate: light chamfer (LDLCha), chamfer (LDCha), shoulder (LDSho) and table top. Teeth were individually weighed to high precision and then prepared following the preparation guidelines. The teeth were reweighed after preparation, and the amount of structural reduction was calculated. In addition, all teeth were scanned before and after preparation, and the 3D volume of removed dental tissue was calculated, superimposing the two .stl files, as a difference of the volumes before and after the preparation. Kruskal–Wallis statistical analysis was carried out to determine significant differences among the groups with a significance level of p  < 0.05. Results: Both analyses showed that LDLCha, ZirKnE and table-top preparations produced the smallest amount of removed structure, whereas the preparations for MCC, ZirSho and LDSho were more destructive. For MCC, 2.6 times more tooth structure must be removed than for table top. ZirKnE was 17.82% and LDLCha was 21.51% more conservative than MCC. The data obtained through the volumetric method were similar with those obtained by gravimetric analysis. Conclusions: ZirKnE, LDLCha, and table-top preparations produced the least amount of tooth tissue removal. Three-dimensional volumetric analysis can be a possible alternative to gravimetric analysis.